Improving the performance of a laser-driven flyer with a diffractive optical element of high wavefront distortion tolerance. (7th July 2021) - Zhang, Yunfei; Qin, Wenzhi; Wang, Liang; Chen, Feiliang; Huang, Xin; Hou, Yidong; Gao, Fuhua
Abstract: To improve the performance of a laser-driven flyer (LDF), we design and fabricate a diffractive optical element (DOE) to convert a laser pulse with nonuniform energy into a flat-topped beam, with 77.05% diffraction efficiency and 55.45% mean square error (MSE). The DOE has a high tolerance for wavefront distortion. Within the maximum 3 λ phase fluctuation, the diffraction efficiency of the flat-topped spot maintains around 77.05% and the MSE is 57.47%. In the experiment, the designed DOE has been well achieved through the photolithography and the reactive ion etching technique, and the DOE displays a diffraction efficiency of 75.15% and a MSE of 64.78%. When combining with the LDF, a flyer with high velocity and integrity has been demonstrated experimentally, where the flyer velocity is increased by about 1.16 ∼ 1.52 times due to the generation of high-uniform laser beam from DOE.